2002
DOI: 10.1063/1.1505112
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hole injections in organic light-emitting devices by depositing nickel oxide on indium tin oxide anode

Abstract: An ultrathin layer of nickel oxide ͑NiO͒ was deposited on the indium tin oxide ͑ITO͒ anode to enhance the hole injections in organic light-emitting diode ͑OLED͒ devices. A very low turn-on voltage ͑3 V͒ was actually observed for the device with NiO on ITO. The enhancement of hole injections by depositing NiO on the ITO anode was further verified by the hole-only devices. The excellent hole-injection ability of NiO was also demonstrated by devising a device with patterned NiO on the ITO anode. Our results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(113 citation statements)
references
References 21 publications
1
111
1
Order By: Relevance
“…3,4 The intrinsic p-type conductivity of NiO x is mainly related to its non-stoichiometric nature where Ni 3+ centers constitute the oxide defects through which holes are transferred. 5 Because of this interesting combination of electrical and optical properties, NiO x has been considered for energy storage applications, [6][7][8] in electrochromic devices as transparent electrode, 9-17 in optoelectronic devices as electron barrier, 18,19 for gas sensing, 20,21 and, more recently, in dye-sensitized solar cells (DSCs) as photoactive cathode. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] The utilization of NiO x in such diverse applications has been accompanied by the development of various preparation methods and deposition techniques, aimed at producing NiO x -based materials with variable chemical composition, electrical resistivity, compactness and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The intrinsic p-type conductivity of NiO x is mainly related to its non-stoichiometric nature where Ni 3+ centers constitute the oxide defects through which holes are transferred. 5 Because of this interesting combination of electrical and optical properties, NiO x has been considered for energy storage applications, [6][7][8] in electrochromic devices as transparent electrode, 9-17 in optoelectronic devices as electron barrier, 18,19 for gas sensing, 20,21 and, more recently, in dye-sensitized solar cells (DSCs) as photoactive cathode. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] The utilization of NiO x in such diverse applications has been accompanied by the development of various preparation methods and deposition techniques, aimed at producing NiO x -based materials with variable chemical composition, electrical resistivity, compactness and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al, suggested that passibility of the NiO x layer formation in the ITO anode could enhance the hole injection in OLEDs because NiO x is a p-type transparent conducting oxide with a high work function. 15 In comparison to an n-type ITO or IZO layer, the p-type NiO x could inject hole carriers more easily into the organic layer. Formation of the NiO x phase in the NIZO layer, which was confirmed by the existence of the Ni 2p and satellite peaks shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] Because the NiO x layer is a well-known p-type conductor with high work function, it is more desirable for hole injection into the organic layer than ITO.…”
Section: 14mentioning
confidence: 99%
See 1 more Smart Citation
“…And several kinds of approaches have been proposed to elevate the work function of ITO, such as using metal oxides with high work functions, inserting conducting polymers between ITO and organic material, and depositing metal-doped ITO layers on the ITO surface. [11][12][13] Iridium oxide ͑IrO x ͒ and ruthenium oxide ͑RuO x ͒ are transparent conducting oxides. The work functions of IrO x and RuO x ͑Ͼ5.0 eV͒ are higher than those of ITO ͑ϳ4.7 eV͒.…”
Section: Introductionmentioning
confidence: 99%